THE TEACHER’S EFFORT TO INCREASE ENGLISH LEARNING ACTIVITIES AT THE ELEVENTH-GRADE STUDENTS OF SMK NEGERI 1 REJOTANGAN DURING PANDEMIC COVID-19 - Azidda, Fazana Ninar (Fakultas Keguruan dan Ilmu Pendidikan Unisda Lamongan, 2023)
This thesis discusses The Teacher’s Effort to Increase English Learning Activities at the Eleventh Grade Students of SMK Negeri 1 Rejotangan During Pandemic Covid-19. Researcher was focused the research on: 1). The teacher’s efforts to increase English learning activities at the eleventh-grade students 2). The inhibiting factors for teacher when increasing English learning activities at the eleventh-grade students 3). The supporting factors for teacher when increasing English learning activities at the eleventh-grade students. This study used a qualitative approach. Research subjects: eleventh-grade English teacher’s, assistant principal of academic. Data collection techniques: observation, interview, questionnaire, documentation. The results of research conducted by researcher are follows: 1). The teacher's effort to increase of English learning activities at SMK Negeri 1 Rejotangan during pandemic Covid-19 can be done by teaching applied by teachers. The teacher designs lesson plans, pays attention to teaching materials and the use of learning media and appropriate learning methods. Therefore, students become motivated to receive, master and develop the material obtained from the teacher 2). The inhibiting factors experienced by teachers when increasing English learning activities are limited interaction, forgetting the lesson schedule, difficult economic complaints from parents, quotas and internet networks that are less than optimal when the learning process takes place, and minimal enthusiasm for learning 3). The supporting factors experienced by teachers when increasing English learning activities are teachers preparing learning tools ranging from lesson plans, media and learning methods, teacher mastery in the field of information technology, student attendance on time according to schedule, good and smooth internet network, and then collecting assignments on time according to the deadline.